2011
DOI: 10.1016/j.orgel.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in high-performance ink-jet printed single-droplet organic transistors based on a silylethynyl substituted pentacene/insulating polymer blend

Abstract: We present a systematic study of the influence of material composition and ink-jet processing conditions on the charge transport in bottom-gate field-effect transistors based on blends of 6,13-bis(triisopropyl-silylethynyl) pentacene (TIPS-PEN) and polystyrene. After careful process optimizations of blending ratio and printing temperature we routinely can make transistors with an average mobility of 1 cm 2 /Vs (maximum value 1.5 cm 2 /Vs), on/off ratio exceeding 10 7 , and sharp turn-on in current (sub-thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 40 publications
5
57
0
Order By: Relevance
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, alignment using inkjet printing is restricted by the registration capability of the instrument, whereas the size of each OTFT is limited by the droplet size attainable (22,31). Another potential issue with these methods is the variance in electrical characteristics of TFTs due to the difficulty in obtaining uniform crystal growth on isolated TFTs over large areas (9,15,21,27,28,(31)(32)(33)(34)(35). Even single crystalline domains of patterned TFTs may have large variability in electrical characteristics as a result of random orientation and size variance.…”
mentioning
confidence: 99%
“…This method was carried out on a patterned substrate, limiting the growth direction of the crystals and allowing the fine control of the crystal location and orientation over a wide area. In a subsequent experiment [457], an SiO 2 -coated Si substrate was patterned into wetting/dewetting regions using OS solution [456][457][458][459] as mentioned earlier. The wetting regions were defined by standard photolithography followed by Cytopℱ spin-coating and annealing at 90°C.…”
Section: Special Os Crystalsmentioning
confidence: 99%
“…There are two methods of inkjet printing in practice, namely, single-droplet printing and multiple-drop printing [459,688,689]. In single-drop printing, each droplet acts as an individual functional deposit, whereas, in the multiple droplets, a continuous film covering the whole area between the source and the drain electrodes forms the active channel.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…This high molecular weight polymer provides mechanical robustness to the film for improved exfoliation while the device performance is not compromised, as shown in recent studies on solution blending of organic semiconductors with organic insulating polymers. [13][14][15][16][17] Thin films were made by spin coating a blend containing 3.6 mg/ml of ActivInk N1400, filtered with a 5 lm filter, and 18 mg/ml polystyrene in chloroform. The perylene bisimide films were annealed in vacuum at 110 C for 1 h to remove residual water and solvents.…”
mentioning
confidence: 99%